PENGARUH LATIHAN TEKNIK TWO BEAT KICK TERHADAP KEMAMPUAN RENANG 50 METER GAYA BEBAS - Meiriani Armen (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2017)
This study aims to determine the effect of two beat kick technique exercises on the 50 meter freestyle. This study was conducted on FIK UNP students who took the basic swimming pool semester january-juny 2008 which amounted to 40 people. Sampling technique was done as many as 20 students students using purposive sampling technique, that is as needed by the researcher. Two beat kick tech data retrieved from 50 meters freestyle test. Two beat kick tech data retrieved from 50 meters freestyle test. Before starting the exercise is done preliminary test (prestest). Being treated in an exercise program with two beat kick techniques for 16 meetings / exercises. The last data is taken by performing the final test (postest). Testing requirements analysis and testing of research hypothesis using data normality test and t-test with significance level α 0,05. From testing the requirements analysis can be obtained the results of normal distributed data training techniques two beat kick with Lcount 0.1279 <Ltable 0.190. From hypothesis testing by using t-test, where tcount 10.8421 and ttable 1.729 which means tcount > ttable there is significant effect of two beat kick technique exercises against 50 meter freestyle freestyle. From the mean technique training obtained two beat kick for pretest time 48.62 and postest 47.59, It can be concluded the two beat kick exercise technique can improve the results of 50 meter freestyle freestyle.